Analysis of Perceived Financial Well-Being and Digital Financial Inclusion: Implications Well-Being of Muslim Women Entrepreneurs - Rohmania, Aftuqa Sholikatur; Nurhapsari, Risma; Sholihah, Erlinda (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study analyzes the impact of current financial management stress, expected future financial security, and digital financial inclusion on Muslim Women Entrepreneurs (WOEs) well-being. From an Islamic perspective, wise budgeting and retirement security are part of the ethical principles of Islamic economics that support individual well-being. Researchers also looked at how self-control functions as a moderating factor in the relationship between the well-being of Muslim WOE and the stress associated with money management today, future financial security expectations, and digital financial inclusion. The hope is to develop knowledge and essential components for achieving success in WOE within Central Java. Using both primary and secondary data sources, this study employs a quantitative methodology and an explanatory research design. Respondents were 200 MSMEs in the food or culinary sector in Central Java whose owners are Muslim women entrepreneurs. Data gathering through questionnaire distribution and analysis using the PLS-SEM method. The study results show that stress in current financial management greatly influences expected future financial security and the well-being of Muslim WOE. In addition, expected future financial security greatly influences well-being, while digital financial inclusion does not show a significant impact. Self-control has been shown to directly affect well-being, although it does not function as a moderating variable. These findings enrich the comprehension of the elements that contribute to the success of Muslim WOE in Indonesia's economic and social context, taking into account the Islamic values ??that underlie economic well-being.